Examination of spectral timbre cues and musical instrument identification in cochlear implant recipients. (March 2014) - Meister, Hartmut; Landwehr, Markus; Lang-Roth, Ruth; Streicher, Barbara; Walger, Martin
Abstract : Objectives: To investigate the discrimination of two isolated spectral timbre cues, spectral centroid (Fc) and spectral irregularity (spIrr), in cochlear implant (CI) listeners. To examine whether the perception of Fc and spIrr changes is related to the perception of loudness and pitch and the identification of musical instruments. Methods: Stimuli were based on French horn recordings which were artificially manipulated with respect to isolated changes in Fc and spIrr. Difference limens for Fc and spIrr were determined and changes in loudness and pitch perception based on these modifications were examined. Identification of musical instruments was additionally assessed. Results: Mean difference limens were 161 Hz for Fc and 0.63 dB for spIrr. Modifications in spectral timbre cues caused changes in loudness and pitch perception. None of the timbre cues examined showed a significant correlation with musical instrument identification. In contrast, instrument identification was significantly related to the frequency of listening to music prior to onset of deafness. Conclusions: CI recipients are able to detect small modifications in spectral timbre cues which are in turn associated with changes in loudness and pitch. Variations of spectral centroid have a larger impact on loudness and pitch perception than variations of spectral irregularity. Music listening behaviour prior to onset of deafness is significantly associated with musical instrument identification.